(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Hair plays an important role in criminal investigation. Due to their close relationship with humans, dogs’ hairs are easily exchanged as they are likely to shed with a slight touch. Different domestic animal species are ranked according to their medullary index, which aids forensic scientists in identifying and comparing various animal hair species. If the hair is from an animal, the forensic investigator may be able to determine which species it came from; the hair could be from a pet or a wild animal; the clues reveal which part of the body the hair came from, if it is human hair; the person’s race, gender, age, and whether the hair was shed naturally or pulled from someone’s body part. The research determines the variations in microscopic characteristics which helps in individualization and differentiation of different breeds. The methodology consisted of sample collections taken from 50 healthy dogs. These hairs are of different breeds of dogs that possesses variations in Fluorescent Microscope with Bright field Digital Microphotography Leica-1000. The result concludes the morphological characteristics like hair colour, hair type, medullary index pattern and micrometric values like medullary index, cuticular index and average hair length of the dog’s breeds. The result also includes the rare finding that is the original Labrador dogs breed shows split ends. -The medullary index gives the exact identification of the